Escrito sobre la ciudad - Solas, Javier G. (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2009)
This paper aims to discuss the relations between the Police, the Advertising, the Private, the Public and the Politics. Cities are full of writings on its urban spaces and architectonic spaces. Those overlapping writings or words show certain forms of domination that confer an image to the city. There are a police writing in the numbers of the buildings, an advertising writing in the signboards and claims, and an expressed political writing in the use of the public space. Living in a time in which the cities want to have a distinguishing image, and they are constituted in tourist announcements, some of them have considered to give back the space to the citizens, creating another image of city.